Holding back the damage: strong political institutions and the effect of populism on business investment - Corina, Margherita; Hartwell, Christopher; Carballo, Alfonso (Journal of International Business Studies, 2025)
Abstract Populism is a political phenomenon that attempts to harness existing institutions for populist ends, often leading to negative consequences for businesses. However, can national institutions resist this pressure and mitigate the damage to firms? This paper investigates how populist electoral success influences corporate investment, unraveling the intricate connection between a country’s political institutions and the investment behavior of companies. Through the lens of political uncertainty and transaction cost economics, we theorize that countries with fortified checks and balances—facilitated by electoral systems (situated at the entrance to power), judicial independence (supervising the exercise of power), and government accountability (serving as ex-post checks)—effectively mitigate populist impulses. However, these checks and balances are also often targeted by populist leaders, as they prevent full implementation of a populist agenda. Analyzing a dataset spanning over 36,000 firms across 42 countries from 1995 to 2021, we find that existing checks and balances shield firms from populist excesses. In line with our theory, the longer a ruler is in power, the weaker these checks and balances remain. Our study highlights populism’s harm to business and the role of robust political institutions as mitigating factors.